2022
DOI: 10.1038/s41598-022-11231-7
|View full text |Cite
|
Sign up to set email alerts
|

On the net primary productivity over the Arabian Sea due to the reduction in mineral dust deposition

Abstract: The dust plume tracks from the Middle East and Eastern Africa to the Indian subcontinent have an impact on the atmospheric and ocean biogeochemistry of the Arabian Sea (AS). Here, we present the impact of dust on net primary productivity (NPP) over the AS using satellite-based observation and model simulation. Seasonal episodes and long-term trends in dust optical depth (DOD), dust mass flux (DMF) and dust deposition flux (DDF) from 2007 to 2020 are quantified. Nearly 32% of the total dust is advected to the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The probable explanation for the negative correlations between Nino3.4-DD and Nino3.4 versus CHL 6-7 months later is that La Niña causes anomalously low precipitation in the dust source regions (i.e., southwestern Asia, the Middle East, and Eastern Africa) that leads to more dust generation during the following summer (Banerjee and PrasannaKumar, 2016). High DD that partially enhanced CHL in August 2006 (Figures 8B, C Because the deposition of dust generated from the same sources mentioned above is important in determining primary production in the Arabian Sea (Tandule et al, 2022) and because we found a significant correlation between DD and CHL in the central/eastern BoB (r = 0.30, Table 2), we suggest that DD plays an important role in determining primary production in the BoB, especially in the central/eastern bay. In addition, the Nino3.4-DD and Nino3.4-CHL (Figure 10) lagged correlations indicated that ENSO influences DD (and hence CHL) in the BoB 6-8 months after the peak of ENSO.…”
Section: Discussionmentioning
confidence: 98%
“…The probable explanation for the negative correlations between Nino3.4-DD and Nino3.4 versus CHL 6-7 months later is that La Niña causes anomalously low precipitation in the dust source regions (i.e., southwestern Asia, the Middle East, and Eastern Africa) that leads to more dust generation during the following summer (Banerjee and PrasannaKumar, 2016). High DD that partially enhanced CHL in August 2006 (Figures 8B, C Because the deposition of dust generated from the same sources mentioned above is important in determining primary production in the Arabian Sea (Tandule et al, 2022) and because we found a significant correlation between DD and CHL in the central/eastern BoB (r = 0.30, Table 2), we suggest that DD plays an important role in determining primary production in the BoB, especially in the central/eastern bay. In addition, the Nino3.4-DD and Nino3.4-CHL (Figure 10) lagged correlations indicated that ENSO influences DD (and hence CHL) in the BoB 6-8 months after the peak of ENSO.…”
Section: Discussionmentioning
confidence: 98%
“…The prevailing consensus is that nutrients are brought to the surface from deeper waters by vertical diffusion or advection, and horizontal circulations redistribute them (Williams and Follows, 1998). The wind-driven Ekman transport controls nutrient dynamics, but the water density controls the NPP rate (Tandule et al, 2022). The major upwelling systems in IO are the western Arabian Sea (WAS), southwest coast of India, Sri Lanka Dome (SLD), Sumatra coast (SC), Seychelles-Chagos Thermocline Ridge (SCTR) (Fig.…”
Section: Water Mass Transport and Mixingmentioning
confidence: 99%
“…Nutrients like iron (Fe), nitrogen (N), phosphorus (P), and silicon (Si) are essential for phytoplankton growth (Bristow et al, 2017). Fe is an important nutrient for photosynthesis (Schoffman et al, 2016) and the aerial deposition of biogenic iron dust can accelerate primary production (Emerson, 2019;Tandule et al, 2022), though ocean contains iron in its dissolved form (DFe). In IO, DFe is high in AS and BoB, with its highest concentration in BoB (0.0018 mmol/m 3 ) during summer and autumn, and the lowest in spring (Fig.…”
Section: Nutrientsmentioning
confidence: 99%